After Jesus Before Christianity : A Historical Exploration of the First Two Centuries of Jesus Movements /: A Historical Exploration of the First Two Centuries of Jesus Movements. (2021) - Vearncombe, Erin; Scott, Brandon; Taussig, Hal; Westar Institute, The
No abstract available